Effect of Temperature induction response on Cell viability, Cell Survivability, Malondialdehyde content and total soluble protein content of cotton (Gossypium hirsutum L.) genotypes - Suneel, D.; Vincent, S.; Babu Rajendra Prasad, V.; Anandham, R.; Raveendran, M.; Rajeeswari, S. (Journal of Phytology, 2022)
“Temperature Induction Response” (TIR) technique was employed to investigate the effect of temperature on popular 20 cotton (Gossypium hirsutum L.) genotypes in a laboratory experiment conducted at the Department of Crop Physiology, Tamil Nadu Agricultural University, Coimbatore during 2020-2021. Identical sized ten days old cotton seedlings were selected and subjected to inductive temperature (gradual temperature raised from 28 to 40℃) for 4 h and non-inductive temperature (46℃ for 3 h, 47℃ for 3 h, 48℃ for 3 h and 48℃ for 4 h) for specific time duration. KC3 and SVPR6 recorded highest thermotolerance among the genotypes and TSH325 and TSH357 showed moderate thermotolerance while TSH375 and TSH383 were sensitive, in terms of seedling survival, cell viability, total soluble protein and malondialdehyde compared to remaining genotypes under non-inductive temperature.